ERROR ANALYSIS OF ASPIRATED AND UNASPIRATED CONSONANT SOUNDS PRODUCED BY STUDENTS AT ENGLISH CLUB SENIOR HIGH SCHOOL OF TRI SUKSES NATAR SOUTH LAMPUNG - Fitri Anggraini (International Conference on Education and Language (ICEL), 2016)
Producing speech sounds is needed for almost speech sound. It is one of elements which is important in language learning. Teaching English especially aspirated and unaspirated consonant sounds requires an effective way especially for teaching English speaking class. The paper analyses the error of aspirated and unaspirated consonant sounds produced by students. Participants are 4 students at English club senior high school of Tri SuksesNatar Lampung Selatan. It is found that there is improvement of aspirated and unaspirated consonant sounds in teaching English.